Load Frequency Control of Three area Multi-Unit Deregulated Power System with FOSMC and Performance analysis using Regulation constant - Vimala Kumar, Kurakula; G.Sritej; V.Ganesh (Politeknik Elektronika Negeri Surabaya (PENS), 2020)
This paper presents three area multi-unit Deregulated Power System (DPS) for Load Frequency Control (LFC) using Fractional Order Sliding Mode Controller (FOSMC) along with Thyristor Controlled Phase Shifters (TCPS) and Superconducting Magnetic Energy Storage (SMES) combination. The FOSMC can be used to overcome nonlinearities and uncertainties of the system for bilateral and unilateral transactions under diﬀerent Step Load Perturbations (SLPs). The deregulated power system performance is analyzed for diﬀerent Regulation constants (R) such as 1.8, 2.4 and 3.0. For stabilization of oscillations in frequency and to stabilize the deregulated power system dynamically for diﬀerent SLPs, TCPS is incorporated with the tie line in series and SMES is used as an energy storage unit. The dynamic responses of LFC problems have been simulated and analyzed with MATLAB/Simulink-based computer simulations. Further simulation results have also been tabulated as a comparative performance with respect to peak overshoot and settling time.